A straightforward microfluidic-based approach toward optimizing transduction efficiency of HIV-1-derived lentiviral vectors in BCP-ALL cells - Seyed Esmaeil Ahmadi; Rima Manafi Shabestari; Amir Asri kojabad; Majid Safa (Biotechnology Reports, 2023)
Background: HIV-1-derived lentiviral vectors (LVs) are capable of transducing human cells by integrating the transgene into the host genome. In order to do that, LVs should have enough time and space to interact with the surface of the target cells. Herein, we used a microfluidic system to facilitate the transduction of BCP-ALL cells. Methods and Results: We used a SU-8 mold to fabricate a PDMS microfluidic chip containing three channels with a 50 μm height and a surface matching 96-well plates. In order to produce LVs, we used HEK293T cells to package the second generation of LVs. First, we evaluated the cell recovery from the microfluidic chip. Cell recovery assessment showcased that 3 h and 6 h of incubation in microfluidic channels containing 100,000 NALM-6 (BCP-ALL) cells with 2μL of culture media yielded 87±7.2% and 80.6 ± 10% of cell recovery, respectively. Afterward, the effects of LV-induced toxicity were evaluated using 10–30% LV concentrations in time frames ranging from 3 h to 24 h. In 96-well plates, it took 12–24 h for the viruses with 20% and 30% concentrations to affect the cell survival significantly. These effects were intensified in the microfluidic system implying that microfluidic is capable of enhancing LV transduction. Based on the evidence of cell recovery and cell survival we chose 6 h of incubation with 20% LV. Conclusion: The results from EGFP expression showcased that a microfluidic system could increase the LV transduction in BCP-ALL cells by almost 9-folds. All in all, the microfluidic system seems to be a great armamentarium in optimizing LV-based transduction.